ANALISIS SEKTOR BASIS DAN PERKEMBANGAN SEKTOR PERTANIAN DI KABUPATEN INDRAGIRI HILIR PROVINSI RIAU TAHUN 2008-2012 - Silaban, Lestari H; Edwina, Susy; ', Eliza2 (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Indonesia is an agricultural country so that the agriculture sector plays an important role and able to give a huge contribution the region's economy. This study aims to identify the primary sector in economy sector, analyze the position and the tranposition of in the agriculture sector and sub-sector in the future, also to analyze the factors that determine the sector transposition in Indragiri Hilir District which can seen of GDP 2008-2012. This research uses secondary data over five years period. Analysis method which used in research is Location Quotient method, Dynamic Location Quotient methods, and the total shift share methods. The results of the research is that agricultural sector plays as a primary sector on Indragiri Hilir’s economy and followed by agricultural sub sector which is holticulture sub-sector, tree crop sub-sector, and fishery sub-sector. And based on combination of Location Quotient and Dynamic Location Quotient analysis methods, known that agriculture sector still will be on primary sector in the future. Horticultural sub-sector, tree crops sub-sector, and fishery sub-sector also will be on primary sub-sector in the future. Agriculture subsector which will have transposition from non primary sector into primary sector is farm sub-sector. By total shift share approaching analysis method, known that the transposition is influenced by economic structural factor. Key words: Agriculture, Location Quotient, Dynamic Location Quotient